Give Yourself Permission to Rest - Kareema J. Gray; Latoya B. Brooks (Genealogy, 2021)
Black women in higher education have always been under pressure to prove that they belong in their positions, and often have taken on more work to prove this. The events of 2020—the COVID-19 global pandemic and the racial and social unrest that swept through the country increased this pressure on Black women in higher education. Historically, Black women have taken on the roles of mother, professional, and caretaker of all who were around them. The events of 2020 added to those roles for Black women faculty, working from home, homeschooling online, checking on the welfare of students, and addressing the emotional needs of their families who have been stuck indoors for months. Self-care is more important now more than before for Black women faculty. To employ these self-care strategies, Black women faculty must first give themselves permission to need them.